Effect Of Health Education About Snack Foods On Snack Food Preferences In Elementary School Students At SDN Jagir 1/393 Surabaya - Eppy Setiyowati; Selvya Alamsyah (Alma Ata University Press, 2019)
Snack food is a type of snack that is very popular with school children and is difficult to separate. School children usually buy snacks without considering their nutritional content. Excessive children's preference for snacks can have a negative impact such as decreased appetite and cause various kinds of diseases due to less hygienic food. The aim of the study was to analyze the effect of health education on snack foods on the preferences (preferences) of snack foods on elementary students at Jagir Elementary School 1/393 Surabaya. Pre-Experimental research design with one group pre-post test design approach. The number of samples is 70 students consisting of grades 4, 5 and 6. Sampling using probability sampling with stratified random sampling technique and using a questionnaire as a measuring instrument. Data were analyzed using Paired T-Test with a significance level of 0.05. The results of the study using Paired T-Test obtained a value of ρ = 0,000 with a significance level of α = 0.05 means ρ <α, then H0 is rejected and H1 is accepted which means that there is an influence of health education on snack foods on snack food preferences elementary school students at SDN Jagir 1/393 Surabaya. The conclusion of this study is that health education has an effect on elementary students on the preference of snack foods. Suggestions, for the school to be taken into consideration in increasing students' knowledge in choosing healthy, safe and nutritious snacks.